PENGARUH MOTIVASI, KESEHATAN DAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN LAPANGAN (Studi Pada PT. Amanah Anugerah Adi Mulia) - Muhammad Fachru Rozy; Hastin Umi Anisah (Universitas Lambung Mangkurat, 2013)
PT. Amanah Anugerah Adi Mulia actively engaged in coal mining operations with considerable occupational risk prone with accidents due to the use of blasting / explosion Companies need to prepare a strategy to motivate employees, many things that can interfere with employee morale should receive attention. Associated with the protection of the health and safety of employees of PT. Amanah Anugerah Adi Mulia always obey the laws and regulations of the K3. The purpose of this study is to investigate and analyze the influence of motivation, health and safety on the performance of field employees. Unit analysis this studies, are field employees who worked in the coal mines owned by PT. Amanah Anugerah Adi Mulia. Research population numbered 200 people with respondents who used as many as 100 employees by sampling random sampling technique. Measurement variables using Likert scale with multiple linear regression analysis using SPSS. The results showed that the variables of motivation, workplace health and safety with ways together (simultaneously) a significant positive effect on performance. Adverbs individually (partial), work motivation, significant positive effect on employee performance, health significant positive effect on employee performance, and work salvation positive and significant impact on employee performance. Variables of work motivation is the dominant variable affecting employee performance